When kingdoms are kingdoms no more: a social-scientific reading of the mustard seed (lk 13:18-19) - Eck, Ernest van (Acta theologica, 2013)
This article presents a social-scientific reading of the parable of the Mustard Seed. It is argued that the parable is not a parable of growth or contrast, and does not allude to the Old Testament. In taking the specifics of the Lukan version of the parable seriously, it is proposed that the Mustard Seed questions religious respectability as understood by the kingdom of the Temple, and undermines imperial interests of the kingdom of Rome.